International Growth Strategies For Small And Medium Enterprises - Aji, Gunawan; Pujianto, Eko; Sa’adiyah Zaen, Addavis; Indriyani, Vivi; Ulufal Qolbi, Ayada (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2023)
The international growth strategy has become increasingly important for small and medium-sized enterprises (SMEs) to enhance competitiveness and expand their market in the era of globalization. SMEs that want to start international expansion must consider several key factors, such as choosing the right products and markets, understanding legal requirements and regulations in the target country, selecting appropriate systems, and building a strong business network. There are also strategic steps that must be taken to improve the growth of small and medium-sized businesses. This research uses a literature review method by examining relevant journals related to the International Growth Strategy for Small and Medium Enterprises. The research is expected to increase knowledge and application in the business world for small and medium-sized enterprises